ANALISIS YURIDIS STRICT LIABILITY KORPORASI PENCEMAR LINGKUNGAN: STUDI KASUS DESA CIKASO BERDASARKAN UNDANG-UNDANG PPLH - Mutiara, Asri Eka (Program Studi Hukum, Universitas Muhammadiyah Sukabumi, 2025)
Environmental pollution in Sukabumi Regency is a serious phenomenon that requires attention and strategic steps, where the contribution of various sectors of life, both individual and communal, is the main causal factor of this problem. This research aims to examine the criminal liability of corporations for environmental pollution. The research method used is descriptive with a normative juridical approach, which explores the criminal liability of corporations for environmental pollution, existing regulations, and practices in the field. The results of the study show that corporations can be held accountable for the crime of environmental pollution. Regulations regarding corporate criminal liability have been regulated in Law No. 32 of 2009, especially Article 116. In this case, the management that gives orders or leads can be held accountable for actions done by, for, or on behalf of the corporation. Thus, strict legal measures against corporations that pollute the environment are essential to protect the ecosystem.